THE FARMER SOCIO-ECONOMIC PROFILE AND MARKETING CHANNEL OF BALI-CALF AT BALI PROVINCE - Ni Made Ayu Gemuh Rasa ASTITI; Ni Ketut Sri RUKMINI; I Gusti Ayu Dewi Seri REJEKI; Roostita L. BALIA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
marketing channel of Bali-cattle has not yet identified and its uncertainty often affected by the socioeconomic profile of the farmer. Several socioeconomic motives such as the need to hold great traditional ceremonies called Ngodalin, marry off their child, build a house, and many others motives that encourage the farmer to sell their Bali-calf to the middleman called Belantik even with an inappropriate price. The study aimed to determine the socioeconomic profile of the farmer and marketing channel of Bali-calf at Bali Province. The research done with the exploratory methods with explanatory research design through survey and the data analysed with quantitative and qualitative approach. The marketing channel of Bali-calf identified at Badung and Buleleng District which chosen by purposive sampling based on the highest Bali-cattle population. The structured questioner used as an interview guideline to help obtain the answer from the respondent, which also equipped with an opened question. The results showed that 90% of respondents are in the productive age, only 6.67% respondents has main job as livestock farmer with average farming experience of 22.18 years. The cattle ownership average is 4.5 cattle/farmer with the motives of livestock farming for savings (48.88%) 48% and the motives for Bali-calf sales is a need for education fee (54%) with traditional ceremonies as the second reason (16.67%). The motives drive vary marketing channel that 73% dominated by direct selling from the farmer to the middleman (Belantik) then the middleman sold the Bali-calf at the animal market the it goes to the slaughterhouse.